Structures and organizations of PSI–AcpPCI supercomplexes from red tidal and coral symbiotic photosynthetic dinoflagellates - Li, Xiaoyi; Li, Zhenhua; Wang, Fangfang; Zhao, Songhao; Xu, Caizhe; Mao, Zhiyuan; Duan, Jialin; Feng, Yue; Yang, Yang; Shen, Lili; Wang, Guanglei; Yang, Yanyan; et al. (Proceedings of the National Academy of Sciences - PNAS, 2024)
SignificancePhotosystem I (PSI) is an efficient photosynthetic supercomplex comprising peripheral antennae and core subunits. During evolution from cyanobacteria to plants, structures of the PSI core are highly conserved, whereas its light-harvesting complexes are varied. We resolved three PSI–AcpPCI structures from two dinoflagellates by cryo-EM, revealing unprecedented changes in the major and minor PSI core subunits. The major PsaA/B subunits are notably smaller and lack more than 20 pigments, whereas PsaD/F/I/J/L/M/R are larger. Their antennae share homologues with those in red algae and diatoms, which are properly assembled with the altered PSI core and organized as an efficient energy transfer network. These results reveal that dinoflagellate PSI–AcpPCI originates from red algae and develops specific characteristics during secondary endosymbiosis. Marine photosynthetic dinoflagellates are a group of successful phytoplankton that can form red tides in the ocean and also symbiosis with corals. These features are closely related to the photosynthetic properties of dinoflagellates. We report here three structures of photosystem I (PSI)–chlorophylls (Chls) a/c-peridinin protein complex (PSI–AcpPCI) from two species of dinoflagellates by single-particle cryoelectron microscopy. The crucial PsaA/B subunits of a red tidal dinoflagellate Amphidinium carterae are remarkably smaller and hence losing over 20 pigment-binding sites, whereas its PsaD/F/I/J/L/M/R subunits are larger and coordinate some additional pigment sites compared to other eukaryotic photosynthetic organisms, which may compensate for the smaller PsaA/B subunits. Similar modifications are observed in a coral symbiotic dinoflagellate Symbiodinium species, where two additional core proteins and fewer AcpPCIs are identified in the PSI–AcpPCI supercomplex. The antenna proteins AcpPCIs in dinoflagellates developed some loops and pigment sites as a result to accommodate the changed PSI core, therefore the structures of PSI–AcpPCI supercomplex of dinoflagellates reveal an unusual protein assembly pattern. A huge pigment network comprising Chls a and c and various carotenoids is revealed from the structural analysis, which provides the basis for our deeper understanding of the energy transfer and dissipation within the PSI–AcpPCI supercomplex, as well as the evolution of photosynthetic organisms.